Diagnostic of residuals from the Buchanan three-phase model used in the fitting of the growth of Chlorella vulgaris cultivated in microfluidic devices (Asian Journal of Plant Biology, 2014)
Nonlinear regression of a data and its subsequent statistical analysis relies on the facts that theresiduals (difference between observed and predicted data) followed a normal or Gaussiandistribution, no autocorrelation and are free of outliers. Previously, we demonstrated that theBuchanan- three phase growth kinetics is the best model using the ordinary least squaresmethod for the growth of the algae Chlorella vulgaris compared to other models such asmodified logistic, modified Gompertz, modified Richards, modified Schnute, Baranyi-Roberts,Von Bertalanffy, Huang and the Buchanan three-phase linear model. If all of these assumptionsare satisfied, the test is said to be robust. In this work we perform statistical diagnostics to theresiduals and discovered the presence of an outlier that allows the residuals to be normallydistributed and satisfy other diagnostic tests after its removal.
Keywords: Buchanan- three phase model, ordinary least squares method, Grubbs test, normal distribution, homoscedastic, autocorrelation